Colorimetric sensing approaches of surface-modified gold and silver nanoparticles for detection of residual pesticides: a review. Issue 15 (8th December 2021) - Singh, Rajat; Thakur, Preeti; Thakur, Atul; Kumar, Harish; Chawla, Prince; V. Rohit, Jigneshkumar; Kaushik, Ravinder; Kumar, Naveen
ABSTRACT: Extensive and erratic use of pesticides leads to bioaccumulation of pesticides in soil, food and waterbodies. Exposure to pesticides is associated with a number of serious diseases, including cancer, birth defects, pregnancy, and many other adverse health effects. Therefore, to protect human health simple and rapid methodologies for monitoring the presence of pesticides in food products are urgently required. Recently, nanoparticles-based colorimetric assays have received great attention for simple and efficient monitoring of pesticide residues. Localised surface plasmon resonance (LSPR) is an important property of metal nanoparticles displaying strong colours in the visible region of the electromagnetic spectrum, where they aggregate and display distinct linear and non-linear optical properties. A well-designed chemical interaction between the surface of nanoparticles and analytes can result in incremental optical changes (red to blue for AuNPs and bright yellow to red-brown for Ag NPs), allowing naked-eye detection of pesticides. These approaches are rapid, cost-effective and used for on-site detection. Furthermore, the sensitivity and selectivity of such assays have been greatly improved through functionalization and modification of nanoparticles. Therefore, in this study, we summarised and explained the recent applications of surface-modified nanoparticles for the detection of residual pesticides. Graphical abstract: uf0001